QUALITY EARLY CHILDHOOD SERVICES A CASE STUDY IN CENTRAL MOLUCCAS, INDONESIA - Deni Agus Panca Susanti (International Conferences on Early Childhood Education Proceedings, 2023)
There are some important points that must be considered, one of which is accreditation to improve the Quality of Early Childhood Services. The quality of Early Childhood Education Service institutions can be measured through assessment indicators on accreditation instruments containing eight national education standards. The objectives of the study are to: a. examine how early childhood service management is viewed from the perspective of management standards to improve institutional quality; b. measure the results of improving the quality of the institution; c. Analyze the problems faced by unit managers in managing early childhood service in terms of Management Standards to improve the quality of the institution; and d. Know the improvement efforts made by early childhood education. The results of the Research manager's analysis compile the Vision and Goals in accordance with the potential of institutions and the environment of early childhood education institutions and make work plans related to eight standards adjusted to budget plans that will be accepted. Coaching is carried out regularly by the Oversight and Foundation, and Managers and teachers are included in the training activities. There are some important points that must be considered, one of which is accreditation to improve the Quality of Early Childhood Services. The quality of Early Childhood Education Service institutions can be measured through assessment indicators on accreditation instruments containing eight national education standards. The objectives of the study are to: a. examine how early childhood service management is viewed from the perspective of management standards to improve institutional quality; b. measure the results of improving the quality of the institution; c. Analyze the problems faced by unit managers in managing early childhood service in terms of Management Standards to improve the quality of the institution; and d. Know the improvement efforts made by early childhood education. The results of the Research manager's analysis compile the Vision and Goals in accordance with the potential of institutions and the environment of early childhood education institutions and make work plans related to eight standards adjusted to budget plans that will be accepted. Coaching is carried out regularly by the Oversight and Foundation, and Managers and teachers are included in the training activities.